2015
DOI: 10.4038/jnsfsr.v43i2.7943
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of industrial wastewaters reaching Dandugan Oya, Sri Lanka using a plant based bioassay

Abstract: Industrial waste may contain complex chemical mixtures with potential cytotoxic and genotoxic effects. The Dandugan Oya, a water canal located in the Western Province of Sri Lanka receives industrial waste from multiple sources. In the present study potential toxicity of selected industrial wastewaters reaching the Dandugan Oya, and the downstream water was assessed using a plant based bioassay with onion (Allium cepa L. var. ascalonicum) as the test organism. Of the physico-chemical characteristics tested, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The occurrence of notched nuclei has also been used as an indication of the presence of components with genotoxic potencial (PAKRASHI et al, 2014;KANNANGARA and PATHIRATNE et al, 2015;BRAHAM et al, 2017;VIANA et al, 2018). Although the pathways of induction and formation have not yet been fully elucidated, the formation of notched nuclei can be attributed to changes in cytoskeletal proteins responsible for the maintenance of the nuclear form (GHISI et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of notched nuclei has also been used as an indication of the presence of components with genotoxic potencial (PAKRASHI et al, 2014;KANNANGARA and PATHIRATNE et al, 2015;BRAHAM et al, 2017;VIANA et al, 2018). Although the pathways of induction and formation have not yet been fully elucidated, the formation of notched nuclei can be attributed to changes in cytoskeletal proteins responsible for the maintenance of the nuclear form (GHISI et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Levels of benzene, mercury, 1,1dichloroethylene, and arsenic in influents to the WWTPs were above the effluent limits for indirect dischargers in industrial complex and average removal rates of volatile organic compounds, metals, selenium and 1,4-dioxane were 70%, 60%, 30% and 18%, respectively, which indicated that managing concerning non-conventional pollutants at each WWTPs is better than establishing a unified limits for all WWTPs. Kannangara and Pathiratne (2015) investigated the toxicity of industrial effluents that were causing negative impacts on the Dandugan Oya, a water canal located in the Western Province of Sri Lanka, using a plant-based bioassay with onion (Allium cepa).…”
Section: Industrial Wastewatermentioning
confidence: 99%
“…Genetic toxicology is involved in detecting compounds capable of causing DNA damage with the aim of understanding potential biological consequences and molecular mechanisms of genetic material. Mutagens screening in environmental samples using in vivo method is reliable to measure the extent of pollution load and this biological assessment is compulsory for effluent discharge from industries before being mixed with watersheds and adjoining territories (Akinboro et al, 2011;de Souza Pohren et al, 2013;Hemachandra and Pathiratne, 2015;Kannangara and Pathiratne, 2015b;Rodrigues et al, 2010). The biological tests, especially short-term bioassays on bacteria or higher plants is the best way to detect and estimate the pollution load in any matrices approach (Gana et al, 2008;Mesi and Kopliku, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on A. cepa results, authors suggested the necessity of stabilization of sewage sludge and soil for a period of at least 12 months since A. cepa test proved to be sensitive tool to assess the efficiency of sewage sludge detoxification process. The physico-chemical characteristics of water from Dandugan Oya, a water canal located in the Western Province of Sri Lanka receives industrial waste from multiple sources along with toxicity using A. cepa was assessed (Kannangara and Pathiratne, 2015a). Root exposed to wastewater and downstream water resulted in the reduction of root growth (24-62%) and mitosis (31-55%), MN (0.6 %), NA (3-14 folds) and CA's (3 -21 folds) in downstream water.…”
mentioning
confidence: 99%